2016
DOI: 10.1039/c6nr07233j
|View full text |Cite
|
Sign up to set email alerts
|

Controlled growth of large-area anisotropic ReS2atomic layer and its photodetector application

Abstract: As an anisotropic 2D layered material, rhenium disulfide (ReS) has attracted much attention because of its unusual properties and promising applications in electronic and optoelectronic devices. However, the low lattice symmetry and interlayer decoupling of ReS make asymmetric growth and out-of-plane growth occur quite easily; therefore, thick flake, dendritic and flower-like structures of ReS have mostly been obtained previously. Here, we report on an approach based on space-confined epitaxial growth for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 33 publications
5
110
0
Order By: Relevance
“…In another study, large-area epitaxial growth of ReS2 on mica support at 500 to 800 o C was reported using ReO3 as a precursor of Re. [45] One critical disadvantage of these processes is using the highly corrosive hydrofluoric acid (HF) as an etchant to delaminate the ReS2 film from the mica substrate. To avoid halogen vapor transport, Bhattacharya et al proposed an alternative approach titled the 'Bridgman method'.…”
Section: Synthesis and Isolation Of Nanolayersmentioning
confidence: 99%
“…In another study, large-area epitaxial growth of ReS2 on mica support at 500 to 800 o C was reported using ReO3 as a precursor of Re. [45] One critical disadvantage of these processes is using the highly corrosive hydrofluoric acid (HF) as an etchant to delaminate the ReS2 film from the mica substrate. To avoid halogen vapor transport, Bhattacharya et al proposed an alternative approach titled the 'Bridgman method'.…”
Section: Synthesis and Isolation Of Nanolayersmentioning
confidence: 99%
“…It is well known that the SiO 2 /Si substrate has a high energy barrier for atom migration due to the rough surface with abundant dangling bonds and defects, which leads to the occurrence of 3D growth. In contrast, the inert and flat surface of mica has a low energy barrier for atom migration, which together with the anisotropic structure of Sb 2 Se 3 favors its epitaxial growth into 1D NW.…”
Section: Performance Of Sb2se3 Nw‐based Photodetectors Synthesized VImentioning
confidence: 99%
“…d) Transfer curves ( I ds − V g ) of the back‐gated ReS 2 FET at various values of V ds . Reproduced with permission . Copyright 2016, Royal Society of Chemistry.…”
Section: Applicationsmentioning
confidence: 99%
“…In addition, the strong anisotropy due to low lattice symmetry endows ReS 2 with interesting characteristics. This indicates that ReS 2 has great potential for a wide range of applications, including anisotropic electronics, photodetectors, logic circuits, and sensors …”
Section: Introductionmentioning
confidence: 99%